2013
DOI: 10.1186/2050-6511-14-33
|View full text |Cite
|
Sign up to set email alerts
|

Effects of packaging and storage conditions on the quality of amoxicillin-clavulanic acid – an analysis of Cambodian samples

Abstract: BackgroundThe use of substandard and degraded medicines is a major public health problem in developing countries such as Cambodia. A collaborative study was conducted to evaluate the quality of amoxicillin–clavulanic acid preparations under tropical conditions in a developing country.MethodsAmoxicillin-clavulanic acid tablets were obtained from outlets in Cambodia. Packaging condition, printed information, and other sources of information were examined. The samples were tested for quantity, content uniformity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 29 publications
3
33
0
Order By: Relevance
“…SFMs were detected due to unsanitary storage conditions, poor adherence to Good Manufacturing Practice (GMP) in the pharmaceutical industries, or illegal production of medicines. For example, we found unacceptable amoxicillin and clavulanic acid tablets during quality testing, as well as metformin extended-release tablets, which dissolved much too quickly [2][3][4]. In addition, some cefixime tablets showed spelling errors on the cartons [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SFMs were detected due to unsanitary storage conditions, poor adherence to Good Manufacturing Practice (GMP) in the pharmaceutical industries, or illegal production of medicines. For example, we found unacceptable amoxicillin and clavulanic acid tablets during quality testing, as well as metformin extended-release tablets, which dissolved much too quickly [2][3][4]. In addition, some cefixime tablets showed spelling errors on the cartons [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, we found unacceptable amoxicillin and clavulanic acid tablets during quality testing, as well as metformin extended-release tablets, which dissolved much too quickly [2][3][4]. In addition, some cefixime tablets showed spelling errors on the cartons [2][3][4]. Although Myanmar is located near Cambodia, research activities were restricted until political reforms were undertaken in 2011 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Authentication of the medicine source via contact with manufacturer, health regulatory agencies, or Internet search has been only attempted in 10/66 (15%) of the selected studies. 12,33,35,40,46,56,62,80,86,88 Package inspection was more popular than authentication, being reported in 39/66 (59%) of studies, with the majority reporting obvious spelling errors and basic label information (medicine name, dosage, manufacturer, expiry date, and lot number), as shown in Tables 1, 2 (61%) and 19/66 (29%) of studies, respectively (Tables 1, 2, and 4). Other chemical analysis methods were reported such as color reaction tests, 39,40,43,48,49,52,[54][55][56][57]66 spectroscopic techniques, 12,43,[54][55][56]58,61,63,69,71,72,75,79,92 and titration, 47,50,52,59,63,73 but remain less frequently used.…”
Section: Type Of Analysis Identified In the Included Studiesmentioning
confidence: 99%
“…Interestingly, only six studies (9%) reported all four types of analysis in an attempt to clearly identify and classify the type of SSFFC problem, where present, in any medicine sample. 33,35,40,62,86,88…”
Section: Type Of Analysis Identified In the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation